1993
DOI: 10.1111/j.1600-0560.1993.tb01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the human hematopoietic progenitor cell antigen CD34 in vascular and spindle cell tumors

Abstract: The human hematopoietic progenitor cell antigen is known as CD34. This antigen is present on normal bone marrow progenitor cells and vascular endothelial cells. We used the monoclonal antibody anti-CD34 and immunoperoxidase staining techniques to evaluate the expression of CD34 in benign and malignant vascular and spindle cell tumors. All of the 42 vascular lesions, except two of three lesions of intravascular papillary endothelial hyperplasia, demonstrated diffuse membraneous staining of moderate to strong in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(84 citation statements)
references
References 19 publications
1
82
0
1
Order By: Relevance
“…15 While initial studies found CD34 positivity in all cases of dermatofibrosarcoma protuberans, subsequent reports indicate that a proportion may be negative for this marker. 10,11,15 Confounding the issue further is the fact that expression of CD34 is not unique to dermatofibrosarcoma protuberans and may be seen in a wide variety of lineage un-related, benign, and malignant neoplasms. 15 More recently, gene microarrays have been used to determine mRNA expression in various tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 While initial studies found CD34 positivity in all cases of dermatofibrosarcoma protuberans, subsequent reports indicate that a proportion may be negative for this marker. 10,11,15 Confounding the issue further is the fact that expression of CD34 is not unique to dermatofibrosarcoma protuberans and may be seen in a wide variety of lineage un-related, benign, and malignant neoplasms. 15 More recently, gene microarrays have been used to determine mRNA expression in various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Expression of CD34, the human progenitor cell antigen and the most commonly used ancillary stain to confirm a histologic diagnosis of dermatofibrosarcoma protuberans, is reportedly positive in most cases of dermatofibrosarcoma protuberans with a sensitivity ranging from 66.6 to 100%. 10,11 Literature indicates that up to 30% of cases of dermatofibrosarcoma protuberans may be CD34 negative. 10,11 This high value may be a reflection of inclusion of cases of cellular dermatofibroma misdiagnosed as dermatofibrosarcoma protuberans; and if one includes cases of dermatofibrosarcoma protuberans that are focally positive for CD34, this number is more likely to be well under 10%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Solitary fibrous tumors have demonstrated strong CD34 immunoreactivity in 79%∂100% of cases (Westra et al 1994). It has also been noted in other tumors such as dermatofibrosarcoma protuberans, smooth muscle tumors, neurofibroma and schwannoma (Traweek et al 1991;Cohen et al 1993).…”
Section: Discussionmentioning
confidence: 89%
“…Histological confirmation also is difficult because of microscopic similarities that exist between these lesions and other soft tissue tumors, namely synovial sarcomas, fibrous histiocytomas, and solitary fibrous tumors. It should be noted that while most hemangiopericytomas express CD-34 as illustrated by our case, the sensitivity of this marker is suboptimal in some cases, often limited to endothelial cells (2).…”
Section: Commentmentioning
confidence: 97%